Circulating miRNA-770-5p and miRNA-30d-5p as potential biomarkers in vasoplegic syndrome after on-pump coronary artery bypass surgery – PREVENT trial. (3rd October 2022) - Mejia, O A V; Souza, R C; Meneghini, B; Santos, A S; Lisboa, L A F; Dallan, L A O; Cunha-Neto, E; Ferreira, L R P; Jatene, F B
Abstract: Introduction: Vasoplegic syndrome (VS) is one of the most common unexpected complications following cardiothoracic surgery, approaching a 25% mortality rate. No standardized methods for diagnosing VS are available. A biomarker is a valuable tool in all fields of medicine, especially in cardiovascular disease when the patient has to undergo invasive surgery as on-pump CABG. MicroRNAs (miRNAs) have been studied and employed as biomarkers for numerous diseases, however, there are no studies regarding their expression in VS. Purpose: To discover a new predictor of VS by comparing the miRNA profiles from patients who evolved to VS versus those who did not evolve after following Coronary artery bypass graft surgery (CABG). Methods: A nested case-control study had an exploratory nature and involved an initial cohort of 87 patients who underwent on-pump CABG in elective or urgency procedures, considering the low surgical risk (STS score <2%). For this analysis, we compared 30 patients, divided into two groups: patients who evolved VS (VASO group, n=15) and who did not evolve VS (NONVASO group, n=15) after surgery. To perform the miRNA profiling, the target prediction, and identify the putative targets of the dysregulated miRNAs, the whole blood samples were collected after anesthetic induction and before incision in the chest (Figure 1A). Results: We identified among the 754 screened miRNAs, eight differentially circulating miRNAs in the whole blood of VASO versus NONVASO groups (Figure 1B). Six miRNAs were increased (hsa-miR-548c-3p, hsa-miR-30d-5p, hsa-miR8 199b-5p, hsa-miR-183-3p, hsa-miR-571, hsa-miR-383-5p) and two were decreased (hsa-miR-1236-3p, hsa-miR-770-5p) and hsa-miR-1236-3p was not statistically significant (Figure 1C). The ROC curves for each single miRNAs yielded the top 2 highest AUC values of 0.8333 and 0.8178 for hsa-miR-770-5p and hsa-miR-30d-5p, respectively. The combination of these two miRNAs yielded an AUC value of 0.9615 with 84.6% sensitivity and 91.67% specificity in distinguishing patients from VASO from NONVASO groups showed a superior diagnostic power to that of a single miRNA (Figure 2). Computational analyses identified as the top enriched pathway the "Apelin Liver Signaling Pathway" with 14 out of 26 molecules within the pathway (53, 8%) containing the higher number of targets of the dysregulated miRNAs. There was no statistical difference in preoperative, postoperative, EuroSCORE II, and variables comparing both groups. Conclusion(s): We showed that miRNA-770-5p and miRNA-30d-5p could be employed as potential biomarkers of VS, a new strategy to VS diagnosis since miRNAs expression could distinguish patients who could and could not evolve the disease. The capability of predicting VS with high accuracy would drastically change the clinical management and patient's referral to cardiac surgery by helping in decision-making once the clinical score risks proved to be unable to predict VS in low-risk patients. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Fundação de Amparo a Pesquisa de São Paulo - FAPESP